The Effectiveness of the Law of the Republic of Indonesia Number 22 of 2009 Concerning Road Traffic and Transportation on Road Accidents - Haki Tiano (UM Purwokerto Press, 2023)
Due to rapidly growing prosperity and the development of traffic technology, the traffic of passengers and goods by motorized vehicles is increasing. This has resulted in an increasing number of traffic accident victims, both drivers and road users. Accidents are caused by three main factors, namely first the human factor, second the vehicle factor, and finally the road factor. Starting from this road factor, the author discusses the causes of traffic accidents. Article 273 of the Road Traffic and Transportation Law Number 22 of 2009 states that the state is responsible for accidents caused by damaged roads. In order to use legal theory as an analytical tool in the research, theories such as the theory of responsibility and the theory of police are used in the handling of events or legal issues raised in the work. The author uses empirical or sociological research methods. The factor that limits the implementation of Article 273 of the Government Transportation Law No. 22 of 2009 is the absence of government regulations that regulate the provisions of Article 273 in more detail. The road administration is responsible for this problem. This uncertainty may affect the application of Article 273 by police authorities. People who do not report accidents due to damaged roads or potholes. Some do not know for various reasons and some do not want to engage with law enforcement officials who treat accidents as accidents. In this case, the police institution itself and the laws made by the government are not implemented because they are related to the government's responsibility.